Understanding bovine embryo elongation: a transcriptomic study of trophoblastic vesicles - Degrelle, Séverine A.; Liu, Fulin; Laloe, Denis; Richard, Christophe; Le Bourhis, Daniel; Rossignol, Marie-Noëlle; Hue, Isabelle (Frontiers in Physiology, 2024)
Background: During the process of elongation, the embryo increases in size within the uterus while the extra-embryonic tissues (EET) develop and differentiate in preparation for implantation. As it grows, the ovoid embryo changes shape into first a tubular and then a filamentous form. This process is directed by numerous genes and pathways, the expression of which may be altered in the case of developmental irregularities such as when the conceptus is shorter than expected or when the embryo develops after splitting. In bovines, efforts to understand the molecular basis of elongation have employed trophoblastic vesicles (TVs)—short tubular EET pieces lacking an embryo—which also elongate in vivo. To date, however, we lack molecular analyses of TVs at the ovoid or filamentous stages that might shed light on the expression changes involved. Methods: After in vivo development, bovine conceptuses (D12 to D18) were sectioned and transferred to a receptive uterus for elongation assessment. In vitro cultured blastocysts (up to D8) underwent the same treatment. Gene expression differences were analyzed across stages using a bovine array (10K) and an extended qPCR array (224 genes, 24 pathways). Results: In vivo, TVs elongated more or less depending on the stage at which they had been created and the time spent in utero. Their daily elongation rates differed from control EET, with the rates of TVs sometimes resembling those of earlier-stage EET. Overall, the molecular signatures of TVs followed a similar developmental trajectory as intact EET from D12–D18. However, within each stage, TVs and intact EET displayed distinct expression dynamics, some of which were shared with other short epithelial models. Conclusions: Differences between TVs and EET likely result from multiple factors, including a reduction in the length and signaling capabilities of TVs, delayed elongation from inadequate uterine signals, and modified crosstalk between the conceptus and the uterus. These findings confirm that close coordination between uterine, embryonic, and extraembryonic tissues is required to orchestrate proper elongation and, based on the partial differentiation observed, raise questions about the presence/absence of certain developmental cues or even their asynchronies.